Effects of High Temperature Stress on mRNA Levels of Ubiquitin-activating Enzyme in Ovarian Tissue of Goldfish, Carassius auratus - Bayir, A.; Polat, M. F.; Aras, N. M.; Nalbantoglu, B. (ACADEMIC JOURNALS INC, 2012)
The stress effect of two different temperatures on mRNA level of ubiquitin-activating enzyme (E1) in ovarian tissue of goldfish was compared. For this purpose, PCR product of 600 bp of E1 was amplified in fish was kept at two different stress temperatures (2 h at+7 degrees C and 2 h at+14 degrees C). At the end of study, there was no any difference between the extent of RT-PCR bands of E1 at 2 h+7 degrees C heat stress and the control group, there was not RT-PCR band of E1 at 2 h+14 degrees C heat stress.
Keywords: E1 enzyme; heat stress; RT-PCR; Carassius auratus; CYCLE MUTANT TS85; EARLY PROTEIN ICP4; PROTEASOME SYSTEM; VIRUS TYPE-1; E1; EXPRESSION; GENE; CELLS; COMPLEMENTATION; GAMETOGENESIS; Veterinary Sciences